DO THIRD-PARTY FUNDS AND BANK RISKS AFFECT THE PROFITABILITY OF DIGITAL BANKS ?: INDONESIAN EVIDENCE - Parlindungan, Salomon; Dewi, Vera; Widyarini, Maria; Soei, Catharina; Candradiningrat, Ica Rika (Faculty of Economic and Business, University of Pasundan, 2024)
This study was conducted on five digital banks in Indonesia, examining the effects of third-party funds (TPF) and bank risks, including credit, market, and operational risks, on profitability. This research employs a quantitative-explanatory approach and uses 96 observational data from five Indonesian digital banks' websites using quarterly financial data from 2019-2023. This study presents novel empirical evidence that the CAR has a positive effect on digital banks' profitability (ROA), and operational risk (OCOI) has a negative effect on profitability (ROA). Using panel data regression, this study finds that TPF and market risks do not significantly affect profitability. The study underscores the crucial role of digital banks' operational and credit risks in profitability while also revealing that TPF and market risk are not among the main drivers of digital banks' profitability.